A Glimpse into Artificial Intelligence in Animal Physiology and Allied Sciences - Ninan , Jacob; Kumar, B.A.A. Sai; Padodara, R. J. (Animal Reproduction Update, 2022)
Artificial Intelligence (AI) has developed as an interdisciplinary science based on computers and is concerned with building machines and equipment which use human intelligence to perform a particular task. The role of AI is manifold in our day-to-day lives. With high penetration amongst people in different societies, AI has transformed the way of living and has the potential to act as a vehicle to disseminate information regarding animal health, production, and reproduction aspects. AI has already made an immense contribution in veterinary and allied sciences by helping in devising various applications used in research and simulation aids. In addition, it has been put in to use efficiently in the field of veterinary sciences thereby hastening diagnosis, treatment, and prognosis of various animal diseases. The history of AI, its applications as software packages in statistics, bioinformatics, simulation apps, and a list of various equipment used for analytical, clinical, and livestock farm purposes are elaborated in this article. Despite playing a vital role, AI has to be further refined in such a way to target the rural livestock farmers to improve animal health and production in developing countries that are in dire need of meeting food security requirements amidst the current scenario of population explosion.